Analysis on the risk factors for organ damage in patients with systemic lupus erythematosus: a cross-sectional single-center experience - Živković, Valentina; Mitić, Branka; Stamenković, Bojana; Stojanović, Sonja; Dinić, Biljana Radovanović; Stojanović, Miodrag; Jurišić, Vladimir (São Paulo Medical Journal, 2019)
BACKGROUND: Organ damage in patients with systemic lupus erythematosus (SLE) occurs as a conse-quence of the disease itself, the therapy applied and the accompanying conditions and complications. Organ damage predicts further organ damage and is associated with an increased risk of death. OBJECTIVE: This study aimed to assess the degree of irreversible organ changes in SLE patients, using the Systemic Lupus International Collaborating Clinics/American College of Rheumatology (SLICC/ACR) damage index (SDI); to establish correlations between organ damage and disease activity, quality of life, intensity of fatigue and serological factors; and to ascertain the risk factors for organ damage. DESIGN AND SETTING: Cross-sectional single-center study conducted at the Institute for Treatment and Rehabilitation “Niška Banja”, Niš, Serbia. METHODS: 83 patients with SLE were enrolled: 58 patients formed the group with organ damage (SDI ≥ 1), and 25 patients without organ damage served as controls (SDI = 0). RESULTS: Organ damage correlated with age (P = 0.002), disease duration (P = 0.015), disease activity (grade 1, P = 0.014; and grade 2, P = 0.007), poor quality of life, severe fatigue (P = 0.047) and treatment with azathi-oprine (P = 0.037). The following factors were protective: use of hydroxychloroquine (P = 0.048) and higher scores obtained for the physical (P = 0.011), mental (P = 0.022) and general health (P = 0.008) domains. CONCLUSION: It is very important to evaluate risk factors for organ damage in the body, including physi-cians’ overall assessment, to try to positively influence better treatment outcomes.